Державне регулювання відносин у сфері банкрутства в національній економіці - Tamosiuniene, Rima; Demianchuk, Maryna; Koval, Viktor (Dr. Viktor Koval, 2019)
Introduction The deepening crisis in numerous business entities of various sizes is due to macroeconomic and domestic political instability, complicated by the consumer credit crisis, as well as tax and administrative pressure. Therefore, the acute problem of bankruptcy of business entities of different sizes and the need to regulate this issue at the state level. Unprofitable business entities of various sizes cause negative consequences for the domestic economy. Aim and tasks. The purpose of the work is to study state regulation of relations in the field of bankruptcy in the economy of Ukraine. Results. The factors, internal and external, preceding the bankruptcy of economic entities. Thus, the external preconditions of bankruptcy are international, economic, political, demographic and others. Internal prerequisites include economic, technical, technological, social and others. The characteristic and gradation criteria of business entities in accordance with legislative acts of Ukraine are presented. It was revealed that the proportion of sales of micro-enterprises is unequal to their share in the total number of enterprises, indicating their negligible contribution to the development of the national economy. According to the results of empirical studies, it was found that during the analyzed period the share of unprofitable enterprises of different sizes is at least a 25%. Such a large number entails not only low financial stability, insolvency and efficiency of business entities themselves, but also inhibits the process of economic growth of the whole country. The application of the method of multivariate discriminant analysis will allow us to draw a conclusion about the financial condition with assigning it a class in accordance with the values of the integral indicator and taking into account the probability of non-fulfillment of obligations, that is, to identify the presence of an unprofitable enterprise and the likelihood of bankruptcy. Conclusions. So, an analysis of the criteria for graduation of business entities made it possible to establish the difference between the administrative and accounting interpretation of the criteria for the attitude of enterprises to various sizes. The dynamics of structural statistics indicators of domestic business entities were monitored, suggesting that individual entrepreneurs make an insignificant contribution to the development of the national economy. Since a quarter of business entities still remain unprofitable, it is necessary to take preventive measures to prevent the loss of solvency by enterprises, one of which is to identify the existence of an unprofitable enterprise and the likelihood of bankruptcy.